Fire Shield : Fire Extinguisher / Ahmad Aslam Mohd Alim - Mohd Alim, Ahmad Aslam (2020)
Nowadays, the level of the awareness about having a fire extinguisher among society is still low although the government has set the targets for the community getting the fire extinguisher since 2012. In getting the fire extinguisher, society faced many issues. One of the problems is that they have to keep the fire extinguisher periodically annually. Fire extinguisher costs are also very high. So, in order to fulfill the government target and also to solve this issue, the company decided to come out with the new fresh idea or concept for the society appliances. As we all know, fire extinguisher should have an inspection yearly in order to maintain it in the best condition and ready to use anytime. The concept that can overcome this issue is the company produce the fire extinguisher that can be inspect by their own. It will save the cost of the maintenance and also can save the time of inspection. This new and fresh product called Fire Shield. Most of the fire extinguishers on the market are a standard fire extinguisher where users need to continuously send the fire extinguisher for inspection, as opposed to the Fire Shield fire extinguisher. Compared to the usual fire extinguisher, several special features which are used in this model. By adding transparent glass window to the fire extinguisher as the mirror that could see through inside the tank, the users could help inspect the fire extinguisher themselves.